Dignity in Death : a critical analysis of whether the right to human dignity serves as appropriate justification for the legalisation of assisted death - Strohwald, Annemarie (Stellenbosch : University of Stellenbosch, 2016)
Research project presented in partial fulfillment of the requirements for the degree of Master of Laws at Stellenbosch University.